STRUCTURAL EQUATION MODELING OF RESIDENTIAL BUILDING ENERGY CONSUMPTION IN RELATION TO OCCUPANT ELECTRICAL HOUSEHOLD USAGE - Hassan Sulaiman, Jibrin; Mohammed Adamu, Abdulrahman (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Despite the nonstop campaigns on global energy awareness and mitigation of Green House Gas (GHG) emissions in the last 50 years, there is more than 100% growth in CO2 emissions annually. If climate change measures are not taken, the global carbon emissions are predicted to rise to 32 billion tonnes of CO2 by 2020. This prediction is expected to double (64 billion tonnes CO2) by 2050. A survey was conducted to analyze how residential building inhabitants use different appliances in relation to energy consumption in Gombe State, Nigeria. The household head is tasked with giving information in response to the questionnaires. Residential owners’ energy consumption was evaluated through the use of a drop-and-pick questionnaire. The survey included electricity energy used in air conditioning system, kitchen appliances, lighting appliances, refrigeration system, bathroom and laundry appliances, as well as other home appliances. The research work employed descriptive design, the study lead to the structured model development as the central focus of the study. A structured questionnaire consisting of 50 items was used as an instrument for data collection. The research population was Labour Housing Estate and Investment Quarters residents of Gombe. The information collected was analysed using descriptive and Confirmatory Factor Analysis. The results were analyzed using the path method tool of Amos 22 software and the correlation tool of Statistical Package for Social Sciences (SPSS). The research indicates that, there is a significant link between dwelling factors and the energy consumption of residential buildings.